2020
DOI: 10.1186/s42234-020-00041-9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation in Parkinson’s disease: a review of the preclinical and clinical data and future prospects

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disease with an incidence of 0.1 to 0.2% over the age of 40 and a prevalence of over 1 million people in North America. The most common symptoms include tremor, bradykinesia, rigidity, pain, and postural instability, with significant impact in quality of life and mortality. To date there is ongoing research to determine the optimum therapy for PD. In this review we analyze the current data in the use of spinal cord stimulation (SCS) therapy for treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Delayed bolus transport to pharynx with altered pharyngeal peristaltic movement may be excitatory-inhibitory reflex rhythm modification 38 as early marker in PD 40,41 . These brainstem reflex rhythms might improve with cervical electric stimulation therapies 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Delayed bolus transport to pharynx with altered pharyngeal peristaltic movement may be excitatory-inhibitory reflex rhythm modification 38 as early marker in PD 40,41 . These brainstem reflex rhythms might improve with cervical electric stimulation therapies 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Then, 3 brief reports of SCS were published, with no extensive descriptions (Soltani and Lalkhen, 39 Mitsuyama et al, 40 and Nishioka and Nakajima 41 ), showing benefits, despite some conflicting results. For a more detailed review of these studies, see Cai et al 43 Table 1 summarizes these findings.…”
Section: Spinal Cord Stimulation and Pdmentioning
confidence: 99%
“…Thereafter, the same group reported that improvement in FoG‐Q scores, FoG episodes, and duration of FoG episodes was sustained in those patients three‐years post‐SCS surgery (97). Additional studies have explored prospective thoracic SCS with moderate benefits (135–137).…”
Section: Targets Of Neuromodulationmentioning
confidence: 99%